Pemaknaan “Ngevent” dengan Perspektif Student Volunteering: Budaya Muda Berdaya dalam Masa Transisi Pemuda - Achmed Faiz Yudha Siregar (Universitas Gadjah Mada, 2022)
This article focuses on individual reflections on ‘ngevent’, which later became ‘slang’ among youths who represent their existence in seeking experiences outside of the campus as volunteers in art and cultural events during their status as students in Yogyakarta. This study is based on a phenomenological study, which uses in-depth interviews, participant observation, and document studies in data collection and is carried out after selecting several participants who have similar experiences in this topic. The findings based on this study show that this experience is proven to be self-enhancing as well as helping to form the values that are attached to identity as agents in youth work who continue to progress through social life. This article explains how the experience is interpreted through construction of the meaning of ‘ngevent’ related to perspectives, motivations, and benefits, as a youth in the context of an late modernity societies that is close to the risk of uncertainty of youth transition in Furlong & Cartmel’s. By using the phenomenological approach with student volunteering perspective and analytical framework of reflexive identity presented by Anthony Giddens help me explain how the social process and the self-construction of the experience, this study found 3 levels of aspect as a result to understand the meaning on the process of ‘ngevent’: External Consciousness, Internal Consciousness, and Oriented Motive & Outcomes. in this end, such experiences can help youth reflection the process & minimize the risk of ‘uncertainty’ in the transition from education to work.